Diagnostic Study of School Opportunities for High School Alumni in the City of Tlalnepantla, State of Mexico - Fernando Briseño Hurtado; Edgar Oliver Cardoso Espinosa; Jorge Mejía Bricaire (Universidad Nacional, Costa Rica, 2014)
It is vital that the school system currently promotes an equal distribution of educational opportunities between all social sectors and encourages alumni to have the opportunity to work in positions where they can take full advantage of the education they received. Therefore, the objective of this study was to diagnose the school opportunities that high school alumni have regarding their academic education and the relationship with their professional and job performance. The research was exploratory since it determined school opportunities for alumni as well as descriptive since it identified means for work insertion, continuity in higher education, and the degree of satisfaction of the educational services received. The design was cross-sectional because data was collected at one specific point in time, using a 44-item questionnaire applied to 65 alumni (36 male and 29 female).  Results showed that the jobs they have are similar to those of their parents: 36.9% employees and 13.8% laborers. Only 41.5% were able to continue with higher education in public institutions, which reflects that poor students are disadvantaged due to their socio-economic and cultural background.